Fabrication of supramolecular hyperbranched polyamidoamine–dextran conjugates and their self-assembly in the presence of EGCG. (13th November 2018) - Hu, Bingshen; Pei, Fanfan; Sun, Xiaoyi; Liang, Yuqing; He, Zhiyong; Zhang, Lili; Li, Juan
Abstract : A supramolecular hyperbranched conjugate, HPAM–Dex, was prepared and it could self-assemble into size-controllable micelles in the presence of EGCG. Abstract : In this paper, a novel double-hydrophilic supramolecular hyperbranched polyamidoamine–dextran (HPAM–Dex) conjugate was synthesized via host–guest interactions of hyperbranched polyamidoamine containing β-cyclodextrin (HPAM-CD) and adamantyl-modified dextran (Dex-Ad). Then, supramolecular polymeric micelles, EGCG–HPAM–Dex, were prepared by directly mixing HPAM–Dex conjugates with hydrophilic (−)-epigallocatechin-3-gallate (EGCG) in aqueous solution. Variable factors on the self-assembly of the EGCG–HPAM–Dex micelles were investigated. Under optimal conditions, the obtained EGCG–HPAM–Dex micelles had an average diameter of 100–200 nm with controllable size and narrow distribution. 1 H NMR, TEM and SEM results indicated that the EGCG–HPAM–Dex micelles were spherical with a core–shell structure. The formation of EGCG–HPAM–Dex micelles is attributed to electrostatic interactions, hydrogen bonding and hydrophobic interactions. The MTT assay reveals that the HPAM–Dex conjugates have lower cytotoxicity than pristine HPAM owing to the introduction of dextran. The stability and the drug loading and release behaviors of the EGCG–HPAM–Dex micelles were also studied.